The Long-Term Effectiveness of the Family Check-Up on School-Age Conduct Problems: Moderation by Neighborhood Deprivation - Shaw, Daniel S. (Dev Psychopathol, 2015)
Several studies suggest that neighborhood deprivation is a unique risk factor in child and adolescent development of problem behavior. We sought to examine whether previously established intervention effects of the Family Check-Up (FCU) on child conduct problems at age 7.5 would persist through age 9.5, and whether neighborhood deprivation would moderate these effects. In addition, we examined whether improvements in parent-child interaction during early childhood associated with the FCU would be related to later reductions in child aggression among families living in the highest-risk neighborhoods. Using a multisite cohort of at-risk children identified on the basis of family, child, and socioeconomic risk and randomly assigned to the FCU, intervention effects were found to be moderated by neighborhood deprivation, such that they were only directly present for those living at moderate versus extreme levels of neighborhood deprivation. Additionally, improvements in child aggression were evident for children living in extreme neighborhood deprivation when parents improved the quality of their parent-child interaction during the toddler period (i.e., moderated mediation). Implications of the findings are discussed in relation to the possibilities and possible limitations in prevention of early problem behavior for those children living in extreme and moderate levels of poverty.